Tenascin-C regulates CXCR4+ B cell migration and cortex formation in the developing bursa of Fabricius - Soós, Ádám; Szőcs, Emőke; Halasy, Viktória; Jurenka, Csenge; Nagy, Nándor (Frontiers in Immunology, 2025)
The bursa of Fabricius (BF) is a unique primary lymphoid organ critical for B cell development in its specialized follicular microenvironment. Although the role of the follicular medulla required for B cell maturation is well characterized, the cellular components and function of the ontogenetically later emerging cortex remain less understood. Here, we combined immunocytochemistry, RNAscope, cell culture, and embryo manipulation techniques to investigate the origin and structure of the cortical compartment. Immunostaining of adult BF revealed a heterogeneous B cell distribution in the cortex, with chB6+/CXCR4high cells in the outer region and CXCR4low/dim cells adjacent to the cortico-medullary border. The cortex is supported by CXCL12+/desmin+/vimentin+ mesenchymal reticular cells producing extracellular matrix (ECM), including tenascin-C, which is enriched in the CXCR4low/dim region. Embryonic expression of tenascin-C coincides with the accumulation of CXCR4+ B cell precursors in the presumptive cortical compartment. Functional studies demonstrate that tenascin-C inhibits embryonic CXCR4+ B cell migration, with overexpression disrupting follicle formation. These findings highlight tenascin-C as a key regulator of B cell migration in the embryonic BF and emphasize the importance of a tenascin-C-free mesenchymal environment for the homing of CXCR4+ B cell precursors during development. In adults, the complementary expression patterns of tenascin-C and CXCR4 molecules suggest that downregulation of CXCR4 is required for B cell migration through the CXCL12-tenascin-C-rich cortex before exiting the BF.